Challenges in Using Modular Approach in Mathematics to Senior Students in Zambales Philippines - Kwajalynne C. Alegre; Teresita A. Falle (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study aimed to identify challenges faced by Grade 11 Senior High School students in using a modular approach for learning Mathematics in the San Felipe District, Division of Zambales, during the school year 2020–2021. A descriptive research design was employed, and data was collected through a questionnaire from 144 randomly selected student respondents. The findings revealed that the student respondents were typically female teenagers, with fathers working as farmers and mothers as housekeepers. The students rated the challenges of using the modular learning approach as